(untitled) (Medico Legal Update, 2021)
Background: Diabetes mellitus (DM) is a significant worldwide medical issue that causes high human, social, and financial expenses on nations at all pay levels. The constant hyperglycemia of diabetes is related to long-term damage, brokenness, and disappointment of different organs, particularly of the eyes, kidneys, nerves, heart, and blood vessels. Method: A descriptive correlational design is used in this study which aims to measure health-related experiences and lifestyle behaviors for clients with type 2 diabetes for the period from (1st October 2019 to 27th August 2020). The study included a convenience sample of 358 clients with type 2 diabetes mellitus who were recruited from Al-Diwaniya Teaching Hospital at Diabetes and Endocrine Center. Data were collected using a self-report study instrument that includes the socio-demographic sheet, the health profile, and the Type 2 Diabetes and Health Promotion Scale. The data were analyzed using Statistical Package for Social Sciences (SPSS) version 26 using the frequency, percent, arithmetic mean, standard deviation, Pearson correlation, Independent-sample t-test, and one-way analysis of variance (ANOVA). The study results displayed that most of participants reported poor Physical Activity level (n = 266; 74.3%), more than two-fifth reported good Risk Reduction level (n = 148; 41.3%), less than two-fifth reported good Stress Management level (n = 134; 37.4%), less than two-fifth reported fair Healthy Diet level (n = 135; 37.7%), more than two-fifth reported good overall behavior (n = 193; 53.9%). Furthermore, there are statistically significant inverse correlations between participants’ age and their Physical Activity, Risk Reduction, Stress Management, Enjoying Life, and overall behavior. Conclusion: The researcher concluded that the younger the clients, the poorer the Physical Activity, Risk Reduction, Stress Management, Enjoying Life, and overall behavior; the older the client, the better the Health Responsibility; the better socioeconomic status, the better the Physical Activity, Risk Reduction, Stress Management, Enjoying Life, and overall behavior.